South Africa : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
This paper discusses South Africa's recent growth performance and its new growth targets. It analyzes the history of exchange rate volatility, compares it with other countries, and examines the relationship between volatility and trade flows in South Africa. It highlights facts on reserves holding and presents an empirical analysis of a model in assessing the adequacy of South Africa's reserves. It also analyzes the cyclical balances to determine revenue performance and discusses the penetration of the South African financial conglomerates into State Security Agency and assesses potential vulnerabilities.